Challenges and Solutions in the Implementation of Educational Policies in Indonesia: A Literature Analysis of Merdeka Belajar Kampus Merdeka and Teacher Reform - Tobondo, Yuyun Alfasius (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study investigates the obstacles and solutions in implementing educational policies in Indonesia, focusing on the 2013 Curriculum and the Merdeka Belajar Kampus Merdeka (MBKM) policy. The objective is to enhance the quality of education by identifying challenges and proposing effective strategies. The research method used is a Systematic Literature Review (SLR), analyzing relevant literature. The findings indicate that the primary challenges include inadequate infrastructure and a lack of policy understanding. Recommendations from the study emphasize the need for improved teacher training, infrastructure development, and enhanced communication strategies. This research offers both theoretical and practical insights for developing more effective and integrated educational policies.